Tense Polyadic N × M-Valued Łukasiewicz–Moisil Algebras - Figallo, Aldo V.; Pelaitay, Gustavo (Bulletin of the Section of Logic, 2015)
In 2015, A.V. Figallo and G. Pelaitay introduced tense n×m-valued Łukasiewicz–Moisil algebras, as a common generalization of tense Boolean algebras and tense n-valued Łukasiewicz–Moisil algebras. Here we initiate an investigation into the class tpLMn×m of tense polyadic n × m-valued Łukasiewicz–Moisil algebras. These algebras constitute a generalization of tense polyadic Boolean algebras introduced by Georgescu in 1979, as well as the tense polyadic n-valued Łukasiewicz–Moisil algebras studied by Chiriţă in 2012. Our main result is a representation theorem for tense polyadic n × m-valued Łukasiewicz–Moisil algebras.